Implementasi Sensor Light Dependent Resistor (LDR) Dan LM35 Pada Prototipe Atap Otomatis Berbasis Arduino - Satriyan Utama; agus Mulyanto; muhammad Arif Fauzi; Novia Utami Putri (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2018)
In designing and making an automatic roof tool that serves to help humans in terms of drying clothes, when exposed to rain then automatically the roof will be closed by itself because this tool uses raindrop sensor, and in cloudy / dark weather conditions the roof will be automatically closed, while at the time bright roof is open by itself, because it uses LDR (Light Dependent Resistor) sensors that can read the intensity of light. In order for the roof to open and close automatically this tool uses a rotating servo 180 degrees. This tool also uses a temperature sensor to determine the condition of the room during rain, cloudy, and bright. How this tool works when the weather conditions outside the bright LDR (Light Dependent Resistor) will read the intensity of light received and has been entered, then the servo will open the roof 180 degrees, and at that time the clothes are being sun-dried can be exposed to the sun, then otherwise if the outside conditions are overcast / dark servo will close the roof 0 degrees. And if the rain is outside raindrop sensor conditions will read the raindrop rain drops and then servo will close the roof 0 degrees so that clothes are dried sdang not be exposed to rain, so we no longer need to back and forth warmed and drying back clothes.